Factory of the Future – new solution and new quality in scientific instrumentation. (March 2019) - Novikov, Dmitry; Veretennikov, Alexander; Borodin, Alexey; Snedkov, Alexander
Abstract: Scientific instrument making is one of the key drivers for the economy of a highly developed country. R&D and manufacturing of scientific devices and equipment in the Russian Federation have been facing a lot of different obstacles during recent decades. The weak link is the transition of the results of fundamental and applied research into prototypes of products, as well as the subsequent organization of mass production. In particular, the problem is the lack of seamless knowledge transfer processes from researchers to developers, as well as the extremely high price of manufacturing samples of scientific instruments and equipment. In this paper we consider the state of art concept of Future plant implementation for scientific instrument making. We also demonstrate an example of successful using of digital technologies in high-tech equipment development project.